Chapter 30 - Dairy production: microbial safety of raw milk and processed milk products - Victor Ntuli; Thulani Sibanda; James A. Elegbeleye; Desmond T. Mugadza; Eyassu Seifu; Elna M. Buys (Academic Press, 2022)
Dairy production is important for the survival of billions of people across the globe who consume milk and dairy products every day. Milk and its products are a source of essential nutrients, such as proteins, fats, vitamins, and minerals necessary for human health. The production and consumption of dairy products are increasing worldwide. As the single most important raw material in dairy production, the quality of raw milk is central to the quality and safety of all dairy products. Owing to its highly nutritious nature, milk serves as an excellent growth medium for a wide range of microbes. Microbial contamination of milk and dairy products along the value chain remains a daunting task for the dairy industry. Notwithstanding the different process technologies (both conventional and novel) that have been adopted by the dairy industry, microbial spoilage of milk and its products still causes major losses in the industry. Furthermore, several foodborne disease outbreaks have been implicated in milk and dairy products around the world. Enteric pathogens such as Salmonella serovars, Campylobacter spp., Shiga toxin-producing Escherichia coli, Listeria monocytogenes, and enterotoxin producing Staphylococcus aureus are the most commonly implicated organisms in dairy-borne disease outbreaks. In order to manage food safety in the dairy industry, any approach to food safety reform must be proactive and risk-based. However, this approach is still posing a challenge in developing countries where the dairy sector is predominated by the informal value chains. Irrespective of the scales of production (large or small scale) and sector (formal or informal), the dairy industry should apply principles of good hygiene practices and good manufacturing practices, coupled with identification and management of possible sources of contamination, in order to curb the challenges of quality and safety.